The Development of Reading Teaching Material through Phonics Method for Kindergarten Students at DD2 School Medan in 2023/2024 - Yohana, Siti; Tambusai, Azhari; Asnawi (PT Inovasi Pratama Internasional, 2024)
Several factors influence the teaching and learning process. The first is students. They have different interests, abilities, and behaviours, which will affect their achievement in learning English. Motivation is a basic factor in the teaching and learning process in the classroom. Students who are highly motivated will be active, but students who are low motivated will be passive and disturb other students. The Development Model in this study will be conducted to develop the phonics method as a method in teaching reading materials for kindergarten students. To achieve this goal, a research approach is needed that highlights efforts to produce reading teaching strategies. Therefore, in designing the model, researchers used the Research and Development approach by adapting the Borg and Gall model.Based on the result of the research and development carried out, it can concluded that developing reading materials through the phonics method designed by researchers aims to help students read simple sentences in English. The development of reading materials through the phonics method that has been designed by researchers has passed the validation stage by 2 expert validators. The effectiveness of reading material through phonics method for kindergarten students at DD2 School Medan that has been developed by researchers can be seen from the results of the effectiveness test.